Atomistic insights into the mechanical properties of CoCrFeMnNi alloy at various strain rates and grain sizes - Tan, Jason Xin An (Nanyang Technological University, 2022)
This project presents atomistic insight into the CoCrFeMnNi alloy. This was done by conducting two sets of tensile tests on the alloy, the first set was done under different temperatures, while the second was done with alloys of different grain sizes. It has been found that with increased temperatures, the strength of the alloy would drop. And, with larger grain sizes, alloy strength would also fall. The strength and dislocation densities of the alloy under these different conditions was analysed with conclusions made to find the alloy with the most ideal properties. These tests were done using software, such as Atomsk and LAMMPS, to run simulations with the stated conditions. Results (dislocation density, type of dislocation etc.) were gathered and analysed using the software OVITO. Stress-strain curves were also plotted using collected values. In all, results observed in this project were aligned with existing research done.